Cryptic polychaete diversity: a review. (16th December 2013) - Nygren, Arne
<x xml:space="preserve">Abstract</x> This review summarises the current knowledge on cryptic species of polychaetes, one of the most dominant taxa in marine communities, and gives a brief overview of the different methods that has been used for their disclosure. Cryptic species constitute an important part of biodiversity and they are common among all kinds of polychaetes, with different life history traits, and may have sympatric as well as allopatric distributions. It is emphasised that cryptic species must not be neglected for a variety of reasons, and even though the magnitude of cryptic species is largely unknown the available data on polychaetes clearly demonstrate that morphology alone seriously underestimate the number of species. It is suggested that future research should focus on appropriately designed case‐studies using combined approaches, as well as on large‐scale whole sample analyses using next‐generation sequencing in order to be able to answer the many questions that still remains.